The "Regulator" Function of Viruses on Ecosystem Carbon Cycling in the Anthropocene - Yang Gao; Yang Gao; Yao Lu; Yao Lu; Jennifer A. J. Dungait; Jennifer A. J. Dungait; Jianbao Liu; Jianbao Liu; Shunhe Lin; Junjie Jia; Junjie Jia; Guirui Yu; et al. (Frontiers Media S.A., 2022)
Viruses act as "regulators" of the global carbon cycle because they impact the material cycles and energy flows of food webs and the microbial loop. The average contribution of viruses to the Earth ecosystem carbon cycle is 8.6‰, of which its contribution to marine ecosystems (1.4‰) is less than its contribution to terrestrial (6.7‰) and freshwater (17.8‰) ecosystems. Over the past 2,000 years, anthropogenic activities and climate change have gradually altered the regulatory role of viruses in ecosystem carbon cycling processes. This has been particularly conspicuous over the past 200 years due to rapid industrialization and attendant population growth. The progressive acceleration of the spread and reproduction of viruses may subsequently accelerate the global C cycle.